Self-Heating, Drying, and Dry Matter Losses of Stockpiled Stemwood Chips: The Effect of Ventilation - Paula Jylhä; Saleh Ahmadinia; Juha Hyvönen; Annamari Laurén; Robert Prinz; Lauri Sikanen; Johanna Routa (Energies, 2022)
The comminution of fuelwood for efficient transportation and handling exposes the material to various biological and chemical decomposition processes. The stockpiling of fuel chips can result in significant dry matter losses (DML) and consequent release of CO2 into the atmosphere. The decomposition processes could be controlled by managing the chip moisture content (MC). MC control by utilizing the self-heating of stockpiled stemwood chips together with wind-driven ventilation was tested in a practical storage experiment, using uncovered and plastic-covered piles as references. The data were analyzed with linear mixed models. The predicted DML was 2.4–3.8% during the monitoring period of 5.9 months, but no significant differences appeared between the storage treatments. The increase in the basic density of the chips decreased DML. On average 1.7–3.5% of the recoverable energy content of the chips was lost during the experiment. The predicted average decline in the MC was ca. 4–8 percentage points (p.p.). The MC of the chip samples stored under plastic tarp was 4–5 p.p. lower than those stored in the uncovered piles. Heat generation within the piles was modest due to the high quality of the chips, and the ventilation solution tested only marginally affected the drying process and the mitigation of DML.